Law of value, unequal exchange, land rent and dependency - Osorio, Jaime (2018)
The theoretical discussion about the character of Latin American capitalism continues to generate debates, where subjects go beyond specific proposals about capitalism, and –as it could not be otherwise– extend to different interpretations of Marxism as such. This paper assumes some general problematic points of Marxism and others of relevance related to the particularities of Latin American dependent capitalism.